From Abroad to Home: Content Analysis of Returnee-Migrant Entrepreneurs in India - Kanika Bakshi, Vandana Yadav (European Economic Letters (EEL), 2024)
This study examines the narratives of returnee-migrant entrepreneurs to India, focusing on the reasons for their return and the challenges they encountered while resettling in India. Study has used content analysis on data collected through semi-structured interviews of 40 returnee entrepreneurs to India. Exposure to diverse business environments, global best practice and family has been a driving force behind their return, but returnee entrepreneurs, in our study encountered significant hurdles influenced by various factors. These challenges, rooted in governmental bureaucracy, cultural adjustments, mentorship gaps, lack of trust, and networking disparities. These hurdles often impede the success of returnee ventures in the home country. The paper recommends concentrating on the reintegration plan that these returning entrepreneurs need to obtain the expertise they acquired while abroad, as well as the effect of their return on home country. Addressing these hurdles requires concerted efforts from various stakeholders, including governments, industry players, and support organizations. Streamlining regulatory processes, fostering cross-cultural understanding, providing targeted mentorship programs, combating biases, and facilitating networking opportunities can create a more conducive environment for returnee entrepreneurship, unlocking their potential to drive innovation and economic growth.